Evaluation of the anterior and overall tooth ratios in the Saudi population versus Bolton's standards - Awawdeh, Mohammed; Alsaadi, Waad; Alraddadi, Faris Awadh B.; Alshunaiber, Renad; Alessa, Jood; Alsaeed, Suliman (Frontiers in Pediatrics, 2023)
Understanding tooth-size discrepancy is essential in the process of diagnosis of maxillary and mandibular relationship. Due to the high incidence of tooth-size disproportion, Practitioners should consider the high incidence of tooth-size disproportion when planning treatment for their patients, as in many cases, this can be a hindrance to obtaining an ideal result.practitioners should pay attention to it when planning treatment for their patients, as in many cases this can be a hindrance to obtaining an ideal result. This study aimed to determine the anterior and overall tooth ratios in the Saudi population and compare them with Bolton's standards. A total of 356 patients were recruited. For the anterior ratio, around 25% of the patients had a ratio equal to Bolton's standards (77.2%). Most subjects (53.7%) had a ratio above 77.2%, and the remaining (20%) had a ratio below 77.2%. The mean amount of anterior mandibular excess was 2.17 ± 2.12 mm, and the mean amount of anterior maxillary excess was 2.16 ± 2.08 mm. For the overall ratio, less than half of the participants (43%) had a ratio equal to Bolton's standards (91.3%). Almost 34% had a ratio above 91.3%, while 23% of the participants had a ratio below 91.3%. The mean amount of overall mandibular excess was 2.54 ± 2.37 mm, and the mean amount of overall maxillary excess was 3.31 ± 3.33 mm. The majority of the study sample had an overall and anterior Bolton ratio that is different from the norms of Bolton's standards, with a tendency for increased overall and anterior ratios. Having specific standards for the Saudi population is important for better clinical assessment and treatment outcomes.